Diet and foraging behavior of a female Baird’s tapir (Tapirus bairdi) in a Costa Rican lowland rainforest (UNED Research Journal, 2015)
The Baird’s tapir (Tapirus bairdii) is an endangered neotropical species which has little field research to guide its conservation efforts. For this reason, the diet and foraging activity of a free ranging female was observed for 286 hrs. from June 1995 to April 1996 in Corcovado National Park, Costa Rica. She consumed 126 plant species (percents: 35.2 vines, 34.1 trees, 15.9shrubs, 14.8 herbs). Three plant genera accounted for 40% of her diet for the entire study: Monstera sp. (Areaceae), Persea sp. (Lauraceae), and Psychotria sp. (Rubiaceae). Her food consisted of 67.0% leaf matter, 18.6% fruit, 11.7% stem, 2.1% bark and 0,1% flower. More fruit and bark were consumed in the wet season and more stem in the dry season. Average time spent feeding was 29.7%, standing chewing 33.4%, moving chewing 7.6%, standing not chewing 5.7%, moving not chewing 20.1% and in social encounters 2.1%. In the wet season more time was spent feeding and chewing while moving and less time moving without chewing. Means for number of paces and bites in ten minute periods were 42,9 and 49,7 respectively. More paces and bites were recorded in the wet season. Average biomass consumed per bite (dry wt.) over a three month period was 3.32 g, for a yearly estimate of 4,307 Kg of dry mass. For an estimate of 200 tapirs in the park, total biomass consumed would be about 861,400 Kg yearly. The tapir is an important mammal in the dynamics of neotropical forests for its roles as keystone browser and potential seed disperser.
Keywords: Baird’s tapir; Tapirus bairdii; diet composition; foraging; behavior; Costa Rica.